2015
DOI: 10.1111/jace.13838
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Materials: A New Rapid Synthesis Process for Nontoxic and High‐Performance Tetrahedrite Compounds

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…2). For Tr = Ni, high ZT value at ∼700 K and good thermal stability up to 783 K were confirmed by other research groups, [49][50][51] whereas for Tr = Ni and Zn (co-doped), ZT = 1 has not been followed up so far. Good figures of merit have been demonstrated also for Tr = Mn, 37,52,53 and Tr = Co, 54,55 as well as samples made of mixed natural and synthetic tetrahedrites.…”
Section: Tetrahedrite (P-type)supporting
confidence: 55%
See 1 more Smart Citation
“…2). For Tr = Ni, high ZT value at ∼700 K and good thermal stability up to 783 K were confirmed by other research groups, [49][50][51] whereas for Tr = Ni and Zn (co-doped), ZT = 1 has not been followed up so far. Good figures of merit have been demonstrated also for Tr = Mn, 37,52,53 and Tr = Co, 54,55 as well as samples made of mixed natural and synthetic tetrahedrites.…”
Section: Tetrahedrite (P-type)supporting
confidence: 55%
“…13,59 For Cu 12−x Tr x Sb 4 S 13 , various synthesis techniques have been examined for large-scale TE application. 50,58,[60][61][62] The Te substituted system Cu 12 Sb 4−x Te x S 13 (0 ≤ x ≤ 1) has also been examined. 63 It was expected that excess electrons donated from Te would fill the unoccupied state near the top of the VB.…”
Section: Tetrahedrite (P-type)mentioning
confidence: 99%
“…The mechanochemical synthesis as a version of solid-state approach has been applied for various materials [13][14][15][16][17][18][19][20]. The combination of mechanical alloying and spark plasma sintering has documented the possibility to synthesize high-performance thermoelectric materials with the possibility to scale the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Barbier et al [49] have investigated another processing technique based on a combination of high-energy ball milling of stoichiometric mixtures of elemental powders and spark plasma sintering. This study, performed on the composition Cu 10.4 Ni 1.6 Sb 4 S 13 , has demonstrated that pure, highly dense samples of this tetrahedrite can be synthesized over a reduced period of time (estimated to eight times shorter by the authors) with respect to conventional solid-state synthesis.…”
Section: Scaling Up Tetrahedrite Synthesismentioning
confidence: 99%